Experimental Study on Water Reduction Modification and Efficient Utilization of Coal-Based Solid Waste Slurry - Chengwei Ma; Dayang Xuan; Jialin Xu; Jian Li (Advances in Civil Engineering)
Unreasonable treatment of coal-based solid waste and coal mining damage are important factors that cause negative environmental effects. Overburden isolated grouting, a green mining method, can realize solid waste emission reduction and coal mine impairment mining. Fluidity and economy are important indices to measure the performance of slurry. Although fly ash slurry with a high water‒cement ratio has good fluidity, it is wasteful in terms of water resources, the filling efficiency is low, and tectonic complexity affects its safe production; similarly, gangue powder slurry has good fluidity but comes with a high cost and complex implementation. Here, the relationship between fluidity and water‒cement ratio in fly ash and gangue powder slurries was studied experimentally; the effects of particle size and dosage of gangue powder and polycarboxylic acid water reducer on the water consumption of fly ash slurry preparation were analyzed. Our results show that the fluidities of fly ash and gangue powder slurries increased with increasing water‒cement ratios under laboratory conditions; the fluidity of gangue powder slurry was much higher than that of fly ash slurry under the same water‒cement ratio and particle size conditions. When 50% gangue powder with particle sizes of 40‒45, 50‒55, 60‒70, and 70‒80 mesh was added to make composite slurries, the water reduction rate of fly ash slurry was 20%, 31%, 34%, and 36%, respectively. Adding a 1% polycarboxylic acid water reducer on top of the effect of the gangue powder gave comprehensive water reduction rates of 29%, 44%, 49%, and 53%, respectively. The critical particle size of gangue powder in the fly ash slurry to achieve stable suspension was 0.27‒0.33 mm; when this was exceeded, the precipitation speed accelerated, and the water reduction rate reduced. A flocculation structure exists in fly ash and composite slurries, and the water reducer can breakdown this flocculation structure, increase the proportion of free water, and improve the fluidity of the resultant slurry. This high-efficiency utilization method of coal-based solid waste modified by water reduction can improve the utilization efficiency of coal-based solid waste and improve the effect and safety of grout-filling technology.